2018
DOI: 10.1002/jpln.201800134
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of soil nutrients in forest areas: A case study from subtropical China

Abstract: Soil nitrogen (N), phosphorus (P), potassium (K), and pH are important determinants and indicators of soil fertility and quality. Especially in forest, these soil properties are highly variable in space and time. However, more information on these properties in subtropical forests is needed to improve soil nutrients management and to sustain the productivity of subtropical forests. We collected a total of 838 forest topsoil samples (0–30 cm in depth) based on a 4‐km (E‐W) × 6‐km (S‐N) grid system in subtropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
(79 reference statements)
1
10
0
4
Order By: Relevance
“…Especially, we found that a large portion (38.1-77.7%) of the variation in β deviation was unexplained by environmental and spatial factors. This is consistent with previous studies 13,38 in which 55.2-73% of the variation in soil microbial community composition and diversity was unexplained. Interestingly, we also found that the unexplained portion was greater in regions with relatively low environmental heterogeneity (36-45°N) than in regions with high environmental heterogeneity (18°, 29-33°, and 47°and 53°N).…”
Section: Random Samplingsupporting
confidence: 93%
“…Especially, we found that a large portion (38.1-77.7%) of the variation in β deviation was unexplained by environmental and spatial factors. This is consistent with previous studies 13,38 in which 55.2-73% of the variation in soil microbial community composition and diversity was unexplained. Interestingly, we also found that the unexplained portion was greater in regions with relatively low environmental heterogeneity (36-45°N) than in regions with high environmental heterogeneity (18°, 29-33°, and 47°and 53°N).…”
Section: Random Samplingsupporting
confidence: 93%
“…This is because when N is deficient, plants increase the proportion of root biomass to increase the N uptake capacity of the roots. The biomass of stems, leaves, and whole plants treated with exponential fertilization showed a trend of increasing first and then decreasing with the increase of total N application rate, indicating that proper fertilization promoted the growth of rooted cuttings [23], significantly increased the accumulation of dry matter in seedlings [14,36], while excessive N application caused slight poison to seedlings [15,21,[37][38][39][40], further impeded the seedling growth and biomass accumulation [41,42]. The highest ratio (1.90) of aboveground biomass/belowground biomass at the final harvest occurred with EF2, the lowest (0.76) was attained with the CK, illustrating that ample and stable nutrients supply in the growing medium tended to enhance shoot growth more than root growth [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Geostatistics is based on the theory of regionalized variables [33]. A semi-variogram is chosen to quantify the spatial variation of an environmental variables and derives essential input parameters for kriging interpolation [34,35]. Geostatistics is widely applied to study environmental variables, which contain both random and structural features in their spatial distributions [36].…”
Section: Methodsmentioning
confidence: 99%